People-Place Bonds in the Context of the Phenomenon of Peripherality - Pytka, Paweł; Rodzoś, Jolanta (Regional Barometer. Analyses & Prognoses, 2011)
Bond between man and place are shaped by many internal factors, depending on the man himself and external — depending on the characteristics of the environment. One likely location of the centers of development. This study examines the impact of peripherality on human feelings and attitudes of the inhabited space. The study was conducted in the Bieszczady Mountains, in the county and the Bieszczady Lesko, among junior high school students (age :15–16 years). The study showed that peripheral to some extent shapes the human relationship with the place. Correlations statistically significant at the level found in the following relationship indicators: identification of the village, identification with the region, assess the landscape, a sense of pride in the fact of living in the community and a sense of longing for a place in the event of his leaving. Diversity study of attitudes of young people from various peripheral zones of the local environment can be observed in many other situations. Students living in the depths of the Bieszczady Mountains appear to be more favorably evaluate their surroundings and feel towards him warmer affection than those who live in the area near centers of development.